Handbook of Gas Sensor Materials Properties, Advantages and Shortcomings for Applications Volume 2: New Trends and Technologies - Korotcenkov, Ghenadii; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
The two volumes of Handbook of Gas Sensor Materials provide a detailed and comprehensive account of materials for gas sensors, including the properties and relative advantages of various materials. Since these sensors can be applied for the automation of myriad industrial processes, as well as for everyday monitoring of such activities as public safety, engine performance, medical therapeutics, and in many other situations, this handbook is of great value. Gas sensor designers will find a treasure trove of material in these two books.
Conventional gas sensor materials -- Auxiliry materials -- Materials for specific gas sensors -- Nanostructered gas sensing materials -- Other trends in design of gas sensor materials -- Nanocomposites -- Stability of gas sensing materials and related processes -- Structure and surface modifications of gas sensing materials.
Keywords: Chemistry; Chemistry; Chemistry/Food Science, general